Chronic elevation of endothelin-1 alone may not be sufficient to impair endothelium-dependent relaxation - Grunewald, Zachary I. (Hypertension, 2019)
Endothelin-1 (ET-1) is a powerful vasoconstrictor peptide considered to be causally implicated in hypertension and the development of cardiovascular disease. Increased ET-1 is commonly associated with reduced nitric oxide bioavailability and impaired vascular function; however, whether chronic elevation of ET-1 directly impairs endothelium-dependent relaxation (EDR) remains elusive. Herein, we report that (i) prolonged ET-1 exposure (i.e., 48 hours) of naïve mouse aortas or cultured endothelial cells did not impair EDR or reduce endothelial nitric oxide synthase (eNOS) activity, respectively (p>0.05); (ii) mice with endothelial cell-specific ET-1 overexpression did not exhibit impaired EDR or reduced eNOS activity (p>0.05); (iii) chronic (eight weeks) pharmacological blockade of ET-1 receptors in obese/hyperlipidemic mice did not improve aortic EDR or increase eNOS activity (p>0.05); and (iv) vascular and plasma ET-1 did not inversely correlate with EDR in resistance arteries isolated from human subjects with a wide range of ET-1 levels (r=0.0037 and r=−0.1258, respectively). Furthermore, we report that prolonged ET-1 exposure downregulated vascular uncoupling protein-1 (p<0.05), which may contribute to the preservation of EDR in conditions characterized by hyperendothelinemia. Collectively, our findings demonstrate that chronic elevation of ET-1 alone may not be sufficient to impair EDR.